Self-assembly directed template photopolymerization of perylenebisimide-poly (4-vinylpyridine): nano organization - Shinde, Shekhar; Asha, S. K. (Polymer, 2015)
A perylene bisimide derivative (PDP-UPBIAcry) having hydroxyl moieties at one termini and polymerizable acrylic units at the other termini was supramolecularly complexed with the pyridine units of Poly (4-vinyl pyridine) (P4VP), followed by photoinduced polymerization of the acrylic units to obtain lamellar organization in the <10 nm range. H-1 NMR studies including variable temperature (20 degrees C-70 degrees C) measurements were undertaken in DMSO-d(6) (anhydrous, extra dry) to understand the interaction between PDP-UPBIAcry and P4VP. The aromatic perylene protons of PDP-UPBIAcry registered an upfield chemical shift while the pyridine protons of P4VP exhibited small downfield shift in their 1:1 supramolecular complex. The hydrogen bonding interaction between pyridyl nitrogen and phenolic OH group was also traced in non-polar media like CDCl3 in model complexes of 4-vinyl pyridine (4VP) with PDP-UPBIAcry. Wide angle X-ray diffraction (WXRD) technique was used to study the bulk structure. Transmission electron microscopy (TEM) imaging revealed highly ordered layered assembly formed upon complexation. Observation from DFT energy minimization studies were correlated with X-ray diffraction data of the supramolecular complex [P4VP (PDP-UPBIAcry)](1.0) to understand the nature of packing of PDP-UPBIAcry that lead to the formation of highly ordered lamellar stacks alternating with P4VP. The higher ordering in the supramolecular polymer complex was also confirmed by the quenching of fluorescence and reduced fluorescence life times of thin solid films of the [P4VP Poly(PDP-UPBIAcry)](1.0) sample. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: hydrogen bonding; P4VP; Perylenebisimide

Supramolecular complexes of poly(3‐Hexylthiophene)‐block (and random)‐poly[3‐(2‐(6‐carboxyhexyl)methyl)thiophene] copolymers with perylene bisimide - Shinde, Shekhar (Journal of Polymer Science Part A: Polymer Chemistry, 2018)
Block and random copolymers of poly(3‐hexylthiophene) and poly[3‐(2‐(6‐carboxyhexyl)methyl)thiophene] with side‐chain carboxylic functionality ((P3HT‐b‐P3COOH) and (P3HT‐r‐P3COOH) were developed by Grignard Metathesis (GRIM) polymerization. The carboxylic functionality was introduced in the side chain via the oxazoline route. Both the block and random polythiophene copolymers were complexed with pyridine functionalized perylene bisimide to obtain supramolecular block and random polymer complexes. The complex formation in both systems was confirmed by 1H NMR, WXRD and SAXS studies. An expansion of d spacing upon complex formation was observed in both the block and random copolymer, which could be traced by WXRD. Hole and electron mobilities measured for the supramolecular complexes indicated values which were higher by an order of magnitude for the supramolecular block complex (μh ≈ 2.9 × 10−4 cm2/Vs; μe ≈ 3.1 × 10−6 cm2/Vs) as compared to the random (μh ≈ 1.4 × 10−5 cm2/Vs; μe ≈ 4.7 × 10−7 cm2/Vs) copolymer. These results are indicative of the higher degree of disorder prevailing in the films of random copolymer system compared to the block copolymer.
Keywords: block and random polythiophene; perylene bisi-mide; Self-assembly